How best to 'go on'? Prospects for a 'Modern Synthesis in the sciences of mind - John Cromby (Frontiers Research Topics, 2016)
Psychology straddles areas from the biological to the social and cultural. Within that vast range, there have been recent explosions of interest in neuropsychology, genetics and epigenetics, and the evolutionary bases of mindedness. Correspondingly, there have been conceptual innovations and new empirical evidence in relation to the embodied, social and discursive processes supporting mind and personhood. Simultaneously, awareness of developmental processes and their dynamic interweaving of genetic, physiological, neurological, social and cultural elements has also increased. Might such developments help 'connect the dots' between diverse aspects of mindedness and the contexts within which it arises? Whilst it seems clear that mind is co-constituted of both biological and socio-cultural processes, how might we bring these disparate realms of knowledge together? In a number of these areas, suggestive integrative possibilities have been explored (e.g., predictive processing, embodied and situated cognition, dynamic developmental systems theory) and insights such as a focus on action, 'knowledge as skills', embeddedness and connectivity have been pursued across a range of disciplines. This edited collection of articles bring together such possibilities - and others - in the same forum in order to provide an opportunity to re-visit a recurring discussion within theoretical psychology: The claimed lack of - and potential for - theoretical synthesis and unity. While the chapters range over a number of areas of research, this collection is focused on current prospects for conceptual synthesis within - or convergence of research between - aspects of mind and mindedness. As is clear from the contributions, it highlights integrative conceptual proposals that emphasize action-orientation, process, embeddedness and connectivity - especially between explanatory 'levels'. Beyond specific proposals for integration, several of the contributions explicitly or implicitly expose broader questions about the purpose of psychological research, the epistemological and ontological commitments required, and the relevant social, political and economic contexts within which such research is performed. This is perhaps inevitable since any aim for synthesis of various understandings of mind will - or should - lead to consideration of the general implications, beyond the 'science', that follow from an integrated account of mind and mindedness. Whether or not the contributions in this volume provide insights into profitable paths towards greater theoretical synthesis in the sciences of mind or, alternatively, provide grist for the mill of renewed skepticism over the potential or even desirability of such synthesis is unpredictable. Whichever the outcome, we feel sure that they will help provoke future productive research in, and thinking about, the sciences of mind.